2015
DOI: 10.2215/cjn.09060914
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro–B-Type Natriuretic Peptide Variability in Stable Dialysis Patients

Abstract: Background and objectives Monitoring N-terminal pro-B-type natriuretic peptide (NT-proBNP) may be useful for assessing cardiovascular risk in dialysis patients. However, its biologic variation is unknown, hindering the accurate interpretation of serial concentrations. The aims of this prospective cohort study were to estimate the within-and between-person coefficients of variation of NT-proBNP in stable dialysis patients, and derive the critical difference between measurements needed to exclude biologic and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…The reference change value (RCV) can be calculated to determine the degree of increase that would be considered a clinically meaningful change (over and above analytic and biological variation) [32]. In dialysis patients undergoing monthly measurements, a clinically meaningful change in NT-proBNP required a decrease of 54% or an increase of 119% [33] and for hs-TnT required a decrease of 25% or increase of 34% [34]. Furthermore, the between person variability for both biomarkers in these studies was very high.…”
Section: Discussionmentioning
confidence: 99%
“…The reference change value (RCV) can be calculated to determine the degree of increase that would be considered a clinically meaningful change (over and above analytic and biological variation) [32]. In dialysis patients undergoing monthly measurements, a clinically meaningful change in NT-proBNP required a decrease of 54% or an increase of 119% [33] and for hs-TnT required a decrease of 25% or increase of 34% [34]. Furthermore, the between person variability for both biomarkers in these studies was very high.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the single-point measurement of NT-proBNP, as well as the other biomarkers of hsCRP, IL-6 and adiponection, did not permit accurate evaluation. Fahim et al reported on the within–person coefficient of variation of NT-proBNP in patients under HD [42]. In the Fahim study, weekly and monthly variations of NT-proBNP were 27% and 35%, respectively; however, the values of NT-proBNP in patients with higher NT-proBNP were maintained at higher levels during the monitoring period [42].…”
Section: Discussionmentioning
confidence: 99%
“…Fahim et al reported on the within–person coefficient of variation of NT-proBNP in patients under HD [42]. In the Fahim study, weekly and monthly variations of NT-proBNP were 27% and 35%, respectively; however, the values of NT-proBNP in patients with higher NT-proBNP were maintained at higher levels during the monitoring period [42]. Moreover, the variations of NT-proBNP were not associated with hydration status, inflammation, or cardiac comorbidity [42].…”
Section: Discussionmentioning
confidence: 99%
“…B-type natriuretic peptide (BNP) and N-terminal pro-BNP (NT pro-BNP) may also have a role in predicting CVD and all-cause mortality in ESKD [168]. The between-person variability of NT pro-BNP is considerable in stable HD patients, likely accounted for by differences in fluid status, residual kidney function, dialysis prescription and underlying cardiac pathologies [169]. However, the within-person variation is markedly smaller and thus may be of greater prognostic significance [169].…”
Section: Biomarkersmentioning
confidence: 99%
“…The between-person variability of NT pro-BNP is considerable in stable HD patients, likely accounted for by differences in fluid status, residual kidney function, dialysis prescription and underlying cardiac pathologies [169]. However, the within-person variation is markedly smaller and thus may be of greater prognostic significance [169]. In a prospective cohort study of baseline serum NT pro-BNP levels in 230 PD patients, the adjusted HR for all-cause mortality and cardiovascular mortality of the fourth quartile were 4.97 (1.35-18.28, p = 0.016) and 7.50 (1.36-41.39, p = 0.021) respectively, compared with the first quartile [170].…”
Section: Biomarkersmentioning
confidence: 99%